ASSOCIATION OF SUBCLINICAL HYPOTHYROIDISM WITH METABOLIC SYNDROME: A CROSSSECTIONAL STUDY FROM WESTERN INDIA - Gupta, Hardik R; Sheth, Sanket P; Vaishnav, Bhalendu S (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Metabolic syndrome (MetS) and subclinical hypothyroidism (SCH) both are known to have adverse cardiovascular outcomes. Available studies have shown variable results on the association of SCH with MetS as well as individual components of MetS. We aimed to study the association of SCH with MetS and its individual components of MetS. Methods: This cross-sectional study was carried out in individuals volunteered for health checkup at tertiary care teaching hospital in Western India. About 60 cases with MetS and 120 controls without having MetS were recruited. Demographic data such as history of diabetes mellitus, hypertension, dyslipidemia, blood pressure (BP), waist circumference and serum T3, serum T4, thyroid stimulating hormone, fasting blood sugar, fasting lipid profile, and hemoglobin A1c were collected and statistically analyzed. Statistical analysis was done by using SPSS sav software packages. Chi-square test was used for the comparison of qualitative data. Results: SCH was present in 52 (28.9%) among 180 study participants. SCH was present in 35 (58.33%) participants having MetS and in 17 (14.16%) of controls. There was a strong association between SCH and MetS (p<0.001). Significant association of SCH with diastolic BP (p=0.017) and with central obesity (p=0.004) was observed but not with high-density lipoprotein, triglyceride, hyperglycemia, systolic BP, total cholesterol, and lowdensity lipoprotein. Conclusion: We observed a strong association of SCH with MetS. We also observed significant association of SCH with diastolic BP and with obesity. The finding of this study indicates the need to screen individuals with MetS for SCH. Keywords: Central obesity, Diastolic blood pressure, Hypertriglyceridemia, Hypertension, Cardiovascular morbidity, Inflammation, Insulin resistance, Low-density lipoprotein, High-density lipoprotein. Â